As expressões ‘ser capaz de’, ‘dar para’ e ‘ter como’ na manifestação da modalidade facultativa no português brasileiro contemporâneo - Lima, Liliane Viana (2024)
This thesis aims to describe and analyze the formal and functional properties that characterize the use of the linguistic expressions ‘ser capaz de’, ‘dar para’ and ‘ter como’ as manifestation marks of the category Facultative Modality in contemporary Brazilian Portuguese. These expressions, when used in Facultative modal contexts, acquire the meaning of physical/circumstantial conditions of the occurrence of a certain event or intrinsic/acquired capacities and abilities of a participant. Theoretically based on Functional Discourse Grammar (HENGEVELD; MACKENZIE, 2008) and authors such as Carretero (1992), Olbertz (1998), Palmer (2001), Souza (2016, 2019), Lima (2018), Lima and Prata (2019, 2023), Oliveira (2020), Lanchares (2021), among others, our methodology starts from a theoretical-practical aspect, in which our hypotheses are tested following the top-down path of Grammatical Component levels (Interpersonal, Representational and Morphosyntactic) to identify how the category manifests itself in Portuguese. For this, we used a sample of blogs from Brazil, which form the Corpus do Português (DAVIES, 2009) database. After selecting the sample and performing the qualitative and quantitative analysis by reading the occurrences individually and testing their statistical relevance in the SPSS software, we observed the following results: a) the expression ‘ser capaz de’ was the most recurrent in participant-orientation. Six cases were found that indicate the category’s performance in the Episode layer; b) the expression ‘dar para’ occurred primarily with event-orientation; c) the expression ‘ter como’ was the least recurrent of the three, acting primarily event-oriented. Through statistical analysis, we realized that some categories are decisive for the manifestation of Facultative Modality, such as the “Position of the Speaker in relation to the Facultatively established value”, which affects a chain reaction and determines, for example, the semantic categories of Reality Conditions and Designation of Argument 1, which in turn determines the morphosyntactic categories of Codification of Argument 1, Verbal Tense and Verbal Mood. With this, we hope to broaden the discussions about the category Facultative Modality and contribute to its description and identification of its modal limits.